PELATIHAN DAN PENDAMPINGAN DALAM PEMBUATAN LAPORAN KEUANGAN USAHA KECIL MENENGAH AJIE FS - Clara Verandita (COMMENT: Journal of Community Empowerment, 2022)
Abstract Micro, Small and Medium Enterprises (MSMEs) are economic business activities carried out by individuals, households or business entities in accordance with applicable regulations. This study aims to discuss financial issues, especially regarding the preparation of financial reports based on SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) for individual companies or Micro, Small and Medium Enterprises (MSMEs). This Independent Study Report is written based on experience, research, and field conditions obtained during the Independent Study activity carried out at the Ajie FS Store Bandar Lampung for two months starting from February 11, 2021 to April 12, 2021. The problems faced by MSMEs are: there are some MSMEs who are not familiar with how to prepare financial reports in accordance with applicable regulations. Thus the author will help SMEs in solving the problem by helping the preparation of financial statements. Keywords: UMKM, Financial Reports, SAK EMKM.